Legal Consequences of Unlawful Act in E-Commerce - Hetty Hassanah; Muhammad Margani (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is to determine the legal consequences of unlawful acts committed in e-commerce. The research method used is analytical descriptive, with a normative juridical approach, both through library research and field studies and the data obtained is analyzed in a qualitative juridical manner. Based on the results of the study, it was found that there were many unlawful acts in e-commerce, which resulted in losses for various parties, especially consumers. E-commerce is carried out borderless with the help of the internet, so this information technology can be a medium that helps e-commerce activities to be effective and efficient. However, advances in information technology do not rule out the possibility of violations of the law which may cause harm to other parties. The conclusion is that in Indonesia there are legal provisions governing acts against the law, although it is difficult to apply in cyberspace, they must still be implemented in order to achieve legal certainty and create a sense of justice. Thus the results of this study can be implemented for internet users, especially e-commerce actors, so that detrimental legal violations do not occur